EFFECT OF XENON ON THE STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF THE INTERNAL ORGANS OF RATS WITH DIFFERENT FORMS OF PERITONITIS - Gozhenko, Anatoliy I.; Vasil’ev, Aleksey A.; Sirman, Viktor M.; Nasibullin, Boris A. (Journal of Education, Health and Sport, 2015)
Gozhenko A. I., Vasil’ev A. A., Sirman V. M., Nasibullin B. A. Влияние ксенона на структурно-функциональные характеристики внутренних органов крыс с разными формами перитонита = Effect of xenon on the structural and functional characteristics of the internal organs of rats with different forms of peritonitis. Journal of Education, Health and Sport. 2015;5(5):531-537. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35658 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A531-537 http://pbn.nauka.gov.pl/works/684420 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.04.2015. Revised 15.05.2015. Accepted: 31.05.2015. Влияние ксенона на структурно-функциональные характеристики внутренних органов крыс с разными формами перитонита Effect of xenon on the structural and functional characteristics of the internal organs of rats with different forms of peritonitis А. И. Гоженко, А. А. Васильев, В. М. Сирман, Б. А. Насибуллин A. I. Gozhenko, A. A. Vasil’ev, V. M. Sirman, B. A. Nasibullin ГП “Украинский НИИ медицины транспорта МОЗ Украины”, Одесса SE "Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine", Odessa Summary There was an experiment on the 177 Wistar rats of outbreed rarefaction. The authors were modelling fecal (infectious) peritonitis and traumatic (gunshot) peritonitis. A physiological solution lavage of abdominal cavity saturated with xenon was used as a corrective procedure. The authors stated the positive effect on the enlargement of pathologic process. The positive effect was expressed by depression of intensity and duration of phlogistic changes. In case of traumatic peritonitis (delay of physiological process is typical for it) it is stated the cutting of this time, so all the time of physiological process is cut. Key words: peritonitis, xenon, abdominal cavity organs. Резюме Авторы по результатам исследования 177 крыс линии Вистар аутобредного разведения, у которых моделировали каловый (инфекционный) перитонит и травматический (огнестрельный) перитонит выявили, что промывание брюшной полости физиологическим раствором обогащенным ксеноном оказывает положительное влияние на развитие патологического процесса. Положительное влияние состоит в уменьшении выраженности и продолжительности воспалительных изменений. В случае травматического перитонита, для которого характерна отсроченность физиологического процесса, отмечается сокращение этого времени, т.е. сокращается всё время патологического процесса. Ключевые слова: перитонит, ксенон, органы брюшной полости.